HAK ASIMILASI DALAM PERSPEKTIF HUKUM ISLAM (ANALISIS PERMENKUMHAM NOMOR 10 TAHUN 2020) - Siska Damayanti; Marsaid Marsaid (Tazir, 2021)
The policy of releasing prisoners in an effort to suppress the spread of Covid 19, better known as the Corona virus is the government's authority. Where the Decree of the Minister of Law and Human Rights reads "Deciding on the release of prisoners and children through assimilation and integration is an effort to prevent and save prisoners and children in prisons, special child development institutions, and state detention houses from the spread of COVID-19". This study uses a qualitative method in the form of library research (library research). The materials used in this research are primary, secondary, and tertiary legal materials. The results of this study obtained from the results of this study are the provision of assimilation and integration must be in accordance with the requirements according to the regulation of the ministry of law and human rights number. 10 of 2020 concerning the conditions for granting assimilation and integration rights for prisoners and children in the context of preventing and overcoming the spread of COVID-19. When viewed from Islamic criminal law, the conditions for granting assimilation and integration rights cannot be separated from the main principles of Islamic law, namely by good behavior as long as he is in a correctional institution or as a prisoner. Keywords: Covid-19, Decree of the Minister of Law and Human Rights, Islamic Criminal Law